2023
DOI: 10.3389/fmed.2023.1159616
|View full text |Cite
|
Sign up to set email alerts
|

Oxalate as a potent promoter of kidney stone formation

Abstract: Kidney stones are among the most prevalent urological diseases, with a high incidence and recurrence rate. Treating kidney stones has been greatly improved by the development of various minimally invasive techniques. Currently, stone treatment is relatively mature. However, most current treatment methods are limited to stones and cannot effectively reduce their incidence and recurrence. Therefore, preventing disease occurrence, development, and recurrence after treatment, has become an urgent issue. The etiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 121 publications
0
13
0
Order By: Relevance
“…In patients with gout, abnormal metabolism or insufficient excretion of oxalate ions leads to an elevated level of oxalate ions in the blood, triggering the deposition of oxalate crystals in the joints, causing arthritis. The concentration of oxalate ions in urine is also associated with the formation of urinary stones [ 7 , 8 , 9 ]. As oxalate ions are primarily excreted through the kidneys, the level of oxalate ions in the blood is closely related to renal function.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with gout, abnormal metabolism or insufficient excretion of oxalate ions leads to an elevated level of oxalate ions in the blood, triggering the deposition of oxalate crystals in the joints, causing arthritis. The concentration of oxalate ions in urine is also associated with the formation of urinary stones [ 7 , 8 , 9 ]. As oxalate ions are primarily excreted through the kidneys, the level of oxalate ions in the blood is closely related to renal function.…”
Section: Introductionmentioning
confidence: 99%
“…Kidney stone is a globally prevalent disease, and its incidence and recurrence rates are increasing year by year. , The incidence and prevalence of kidney stones was up to 14.8% and a recurrence rate of up to 50% within the first 5 years of the initial stone episode . Oxalate is a common metabolic end product and a key component of most clinically detected calcium oxalate (CaOx) kidney stones. , …”
Section: Introductionmentioning
confidence: 99%
“…3 Oxalate is a common metabolic end product and a key component of most clinically detected calcium oxalate (CaOx) kidney stones. 4,5 Oxidative stress injury to renal epithelial cells serves as the initiating factor and underlying lesion for the formation of calcium oxalate (CaOx) stones. Prolonged exposure of renal tubular epithelial cells to high levels of oxalate and the presence of CaOx microcrystals lead to excessive production of reactive oxygen species (ROS), which contributes further to oxidative stress damage in the cells.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that a defect in the PAT1 can lead to hyperoxalemia, hyperoxaluria, and the formation of oxalate stones [ 13 ]. This occurs because the deficiency of PAT1-mediated oxalate secretion in the intestine leads to an increase in the net absorption of oxalate, which results in an increase in the concentration of oxalate in the plasma and a higher level of oxalate excreted in the urine.…”
Section: Introductionmentioning
confidence: 99%
“…This occurs because the deficiency of PAT1-mediated oxalate secretion in the intestine leads to an increase in the net absorption of oxalate, which results in an increase in the concentration of oxalate in the plasma and a higher level of oxalate excreted in the urine. In contrast, the overexpression of PAT1 in the intestine can reduce the oxalate concentration in the urine and prevent kidney stone formation [ 13 ]. Therefore, regulating PAT1 expression could be a potential target for treating and preventing kidney stones.…”
Section: Introductionmentioning
confidence: 99%